2000
DOI: 10.1590/s0004-28032000000300008
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cryptosporidiosis as a clue for the diagnosis of the acquired immunodeficiency syndrome

Abstract: -Cryptosporidium parvum has been detected with increasing frequency in the gastrointestinal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
9
0
3
Order By: Relevance
“…Endoscopy may show fold thickening of the mucosa, with an erythematous and granular appearance that is most prominent in the duodenum [49] . In general, duodenal erosions or ulcers are not found.…”
Section: Cryptosporidiummentioning
confidence: 99%
“…Endoscopy may show fold thickening of the mucosa, with an erythematous and granular appearance that is most prominent in the duodenum [49] . In general, duodenal erosions or ulcers are not found.…”
Section: Cryptosporidiummentioning
confidence: 99%
“…While Cryptosporidium sp settles primarily in the gastrointestinal systems of persons having normal immune systems, causing diarrhoea, it can lead to various clinical manifestations (gastritis, sinusitis, cholecystitis, pancreatitis, hepatitis) in extraintestinal sites like the respiratory system in immunodeficient patients (6,13,15). In a study conducted by Clavel et al(16) 57 respiratory cryptosporidiosis cases were reported since 1980 and that all of these cases were immunodeficient patients (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the ileal mucosa is the focus for colonization, although it can also infect the large bowel, stomach, and biliary tract [1]. There have been few reports of isolated gastric Cryptosporidium infestation in HIV-positive individuals; however, to our knowledge, there have been no published cases of isolated gastric Cryptosporidium in HIVnegative patients [2].…”
Section: Introductionmentioning
confidence: 98%